Palm oil industry: A review of the literature on the modelling approaches and potential solution - Zabid, M. Faeid M.; Zainal Abidin, Norhaslinda (2015)
Palm oil industry plays an important role as a backbone to the economy of a country, especially in many developing countries.Various issues related to the palm oil context have been studied rigorously by previous researchers using appropriate modeling approaches.Thus, the purpose of this paper is to present an overview of existing modeling approaches used by researchers in studying several issues in the palm oil industry.However, there are still limited numbers of researches that focus to determine the impact of strategy policies on palm oil studies. Furthermore, this paper introduces an improved system dynamics and genetic algorithm technique to facilitate the policy design process in palm oil industry.The proposed method is expected to become a framework for structured policy design process to assist the policy maker in evaluating and designing appropriate policies.